Patron of all teachers - De La Salle University, Manila (Animo Repository, 1950)
St. John Baptist de La Salle died on April 7, 1719. The Catholic Church celebrates April 7 as his feast day, but La Salle schools celebrate it on May 15. This was the day when St. John Baptist de La Salle was declared by the Church as Patron of all Teachers in 1950.